2020
DOI: 10.1159/000510092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cognitive Functioning and Education on Later-Life Health Numeracy

Abstract: <b><i>Introduction:</i></b> Previous studies have shown an association between a high health numeracy and good cognitive functioning. <b><i>Objective:</i></b> To investigate the moderation effect of education on this relationship and which brain structures support health numeracy. <b><i>Methods:</i></b> We examined 70 healthy older persons (66% females; mean ± SD: age, 75.73 ± 4.52 years; education, 12.21 ± 2.94 years). The participants un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…It is therefore possible that we missed correlations between performance on the COV Numeracy Scale and demographical variables as previously found for other numeracy scales [ 22 ]. In this study, a correlation between education and objective performance was only found for the HNS, in line with previous studies [ 22 , 23 ]. Authors of future studies are encouraged to administer the COV Numeracy Scale to a large stratified sample of participants in order to detect possible variations in performance due to age, education level, and sex.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is therefore possible that we missed correlations between performance on the COV Numeracy Scale and demographical variables as previously found for other numeracy scales [ 22 ]. In this study, a correlation between education and objective performance was only found for the HNS, in line with previous studies [ 22 , 23 ]. Authors of future studies are encouraged to administer the COV Numeracy Scale to a large stratified sample of participants in order to detect possible variations in performance due to age, education level, and sex.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies showed that numeracy is poor among the general population [ 21 ]. It decreases with advancing age [ 22 ] and is low in people with low education [ 22 , 23 , 24 ], older women [ 22 ], and people with poor cognitive abilities (specifically, executive functions and mental calculation) [ 22 , 23 ]. In numeracy tasks, people with neurodegenerative conditions are even more at disadvantage than healthy individuals are [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results can provide new information for the formulation of interventions for adults with DD. Many efforts have been made in the last decades to support students with mathematical learning difficulties [46,47], but attempts to propose age-appropriate trainings for adults with numerical difficulties are rare [48,49]. Our study highlights the need to design innovative interventions that may target deficiencies in the cognitive, numerical, social, and emotional dimensions of adults with DD.…”
Section: Discussionmentioning
confidence: 90%
“…Recent research, indeed, seems to show that this may not be the case: while efficiency in most abilities, like attention, executive functions, working memory, and orientation, is directly and positively related to the amount of CR, evidence has been found that other abilities do not seem to be as sensitive (Lavrencic et al, 2018;Pettigrew & Soldan, 2019). For instance, Arcara and colleagues (2017) showed that CR (including education, working and leisure activities) does not predict aging performance in basic mathematical abilities (which were in fact predicted only by education; see also Zamarian et al, 2020). The reason for this result, may be that, in contrast to other contents of knowledge, basic math notions are specific and learned early at school in a systematic way.…”
Section: Introductionmentioning
confidence: 99%